Numerical simulation of transient cavitation characteristics of valve-controlled liquid-filled hydrodynamic coupling - Cui, Hongwei; Zhang, Jiahua; Li, Li; Wang, Guoqiang (Frontiers in Energy Research, 2023)
In high-power impeller industries, valve-controlled liquid-filled hydrodynamic couplings are widely used in the soft startup of heavy-duty scraper conveyors for mining. However, the water circulation speed in internal flow fields is higher at lower speed ratios, making the hydrodynamic couplings prone to severe cavitation, which further results in severe performance degradation, noise, vibration, or even erosion failure. Meanwhile, because a hydrodynamic coupling is a piece of closed-loop multicomponent turbomachinery, internal transient cavitation flow behavior cannot be easily controlled. To reasonably predict the characteristics of cavitation and its influence on the working performance of the hydrodynamic coupling, a high-quality structured mesh model of the internal flow field for an impeller was established. Considering the periodic structural characteristics of the impeller, a scale-resolving simulation turbulence model was combined with a Rayleigh–Plesset cavitation model to establish a single-cycle hydrodynamic coupling calculation model. The cavitation distribution characteristics and torque transmission of the flow field under different working conditions were obtained, and the effect of cavitation on the soft startup performance was analyzed. The results demonstrated that cavitation in the hydrodynamic coupling mainly occurred under low speed ratios. The degree of cavitation decreased as speed ratio increased. The worst-case scenario for cavitation occurred when the speed ratio was zero. Most of the cavitation bubbles were generated at the tip of the blades, resulting in unstable variation in torque characteristics and deterioration of the working performance of the hydrodynamic coupling. The analysis reveals that the cavitation process in the impeller is highly unstable and periodic, and the cavitation development near the tip of the blades occurs in four stages: birth, growth, separation, and disintegration. The generated steam accumulates in the inner ring of the impeller. Therefore, a method for accurately predicting the cavitation characteristics of hydrodynamic couplings based on high-precision technology is proposed, and a theoretical basis for coupling design and cavitation suppression technology is provided.